Review of Theory of Regular Economies - YANG, Zhenlin (Institutional Knowledge at Singapore Management University, 2005)
This book provides a systematic treatment of the theory of regular economies, one of themost advanced topics in modern general equilibrium theory, emphasizing on the basiceconomic ideas, mathematical tools and important economic applications. By introducingthe necessary mathematical tools, in particular the Differential Topology, graduallywhen needed, Professor Nagata has made this highly mathematical subject understandableto many readers including graduate students in economics. Through the study of variousimportant theoretical problems such as the existence of equilibria, local uniqueness andfiniteness of the set of equilibria, inefficiency of equilibria, etc., Professor Nagata has demonstratedhow successful it is to use mathematics to study important theoretical economicsproblems